Curable polyolefin compositions and cured products
The curable polyolefin composition addresses the challenges of PCM loading and compatibility by formulating a balanced blend of polyolefin, wax, organopolysiloxane, and catalyst, resulting in effective thermal energy storage and release without wax leakage, suitable for electronic device thermal management.
Patent Information
- Application Number
- JP2023551993
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-03
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-03-03
AI Technical Summary
Existing curable compositions that incorporate phase change materials (PCMs) face challenges such as high costs, low reproducibility, and limited PCM loading, leading to inadequate thermal energy storage and release capabilities, as well as issues with PCM leakage during thermal cycling due to compatibility problems with silicone-based materials.
A curable polyolefin composition comprising a polyolefin with aliphatic unsaturated bonds, a wax with a melting point of 30-100°C, an organopolysiloxane with silicon-bonded hydrogen atoms, and a hydrosilylation reaction catalyst, which are formulated to achieve a balanced content of these components to ensure effective curing and prevent wax leakage during thermal cycling.
The curable polyolefin composition effectively stores and releases thermal energy, preventing wax leakage and pressure during thermal cycling, while achieving good phase change properties with an enthalpy of 20-140 J/g, thus providing a reliable thermal management solution for electronic devices.
Smart Images

Figure 0007653531000004 
Figure 0007653531000001 
Figure 0007653531000002
Abstract
Description
[Technical field]
[0001] The present invention relates to curable polyolefin compositions and cured products thereof. [Background technology]
[0002] Phase change materials (PCMs) are known as latent heat storage materials that passively absorb or release large amounts of heat from the surrounding environment by utilizing the phase change of the material itself, and thus have been used in recent years to cool electronic devices such as mobile phones, smartphones and tablets whose power inherently varies over time. The power fluctuations can occur for short time intervals, such as minutes, or for longer time intervals, such as days. When the temperature peaks, the PMC melts and stores the excess heat energy. When the temperature drops, the PMC solidifies and releases the stored heat energy.
[0003] For example, US Patent No. 5,999,633 discloses gel-coated microcapsules containing PCM, which are produced by a sol-gel process to encapsulate PCM particles. However, there are problems with the high cost, low reproducibility of the process, and low loading of PCM. With low loading of PCM, the ability to store and release thermal energy, i.e., the enthalpy of phase change (J / g), is lower than 20 J / g.
[0004] Patent Document 2 discloses a silicone elastomer composition comprising at least one room-temperature vulcanizing (RTV) silicone elastomer and at least one PCM. Patent Document 3 discloses a hot melt sealant / adhesive composition comprising a siloxane polymer, a hot melt resin, and / or an organic resin. However, due to compatibility issues between the PCM and silicone, there is a problem that the PCM is too hard to disperse in the silicone elastomer or siloxane polymer. As a result, the PMC leaks / squeezes out of the cured product during thermal cycling.
[0005] Prior art documents Patent Literature Patent Document 1: U.S. Patent No. 6,270,836(B1) Patent Document 2: U.S. Patent Application Publication No. 2014 / 0030458(A1) Patent Document 3: U.S. Patent No. 8,088,869 (B2) Summary of the Invention
[0006] Problem to be solved by the invention It is an object of the present invention to provide a curable polyolefin composition that can be cured to form a cured product that can store and release thermal energy, and the cured product can prevent wax leakage / extrusion during thermal cycling.
[0007] Means for solving the problem The curable polyolefin composition of the present invention comprises: (A) a polyolefin having at least two aliphatic unsaturated bonds per molecule; (B) a wax having a melting point of 30 to 100°C; (C) an organopolysiloxane having at least two silicon-bonded hydrogen atoms per molecule; (D) a catalytic amount of a hydrosilylation reaction catalyst; Based on the total mass of components (A) to (D), the content of component (A) is 20 to 80 mass%, the content of component (B) is 10 to 75 mass%, and the content of component (C) is 1 to 20 mass%.
[0008] In various embodiments, component (A) is a polybutadiene.
[0009] In various embodiments, component (B) is a wax selected from paraffin wax, microcrystalline wax, or polyethylene wax.
[0010] In various embodiments, the thermal interface material further comprises (E) at least one inorganic filler.
[0011] In various embodiments, component (E) is at least one inorganic filler selected from a flame retardant filler or a thermally conductive filler.
[0012] In various embodiments, component (E) is present in an amount of up to 50% by weight of the composition.
[0013] The cured product of the present invention is obtained by curing the above-described curable polyolefin composition.
[0014] Effect of the Invention The curable polyolefin composition of the present invention can be cured to form a cured product that can store and release thermal energy, and the cured product can prevent wax leakage / pressure during thermal cycling. In particular, the cured product has good phase change properties with an enthalpy of 20-140 J / g, while the cured product is fully cured without wax leakage during thermal cycling. [Brief description of the drawings]
[0015] [Figure 1] For example, it is a Differential Scanning Calorimetry (DSC) chart for measuring the temperature of phase change and the enthalpy of phase change in the examples.
[0016] definition The term "comprising" or "comprise" is used broadly herein to mean and encompass the concepts of "including" or "include," "consist(ing) essentially of," and "consist(ing) of." The use of "for example," "eg," "such as," and "including" to list examples does not limit the examples listed. Thus, "for example" or "such as" means "for example, but not limited to" or "such as, but not limited to," and encompasses other similar or equivalent examples. As used herein, the term "about" serves to reasonably encompass or account for minor variations in numerical values as determined by instrumental analysis or as a result of handling samples. Such minor variations may be as much as ±0-25, ±0-10, ±0-5, or ±0-2.5% of the numerical value. Furthermore, the term "about" applies to both numerical values when relating to a range of values. Furthermore, the term "about" may apply to numerical values even if not expressly stated.
[0017] The term "wax" is used herein to mean a material that is solid at ambient temperature (eg, 25° C.) and exhibits softening or melting properties at elevated temperatures. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The curable polyolefin composition of the present invention will now be described in detail.
[0019] Component (A) is the main component and is a polyolefin having at least two aliphatic unsaturated bonds per molecule. Here, component (A) is a polyolefin with aliphatic unsaturated bonds grafted to the main chain group or a polyolefin whose main chain contains aliphatic carbon-carbon unsaturated bonds. Component (A) may be linear or branched, and may be a homopolymer, copolymer or terpolymer. Component (A) may also be present as a mixture of different polyolefins, so long as there are an average of at least two aliphatic unsaturated bonds per molecule. Examples of polyolefins of component (A) include polyisoprene, polybutadiene, copolymers of isobutylene and isoprene, copolymers of isoprene and butadiene, copolymers of isoprene and styrene, copolymers of butadiene and styrene, copolymers of isoprene, butadiene and styrene, and polyolefin polymers prepared by hydrogenating polyisoprene, polybutadiene, or copolymers of isoprene and styrene, copolymers of butadiene and styrene, or copolymers of isoprene, butadiene and styrene. Among these, component (A) is preferably polybutadiene.
[0020] The aliphatic unsaturated bonds in the molecules of component (A) may be the same or different and may contain 2 or more carbon atoms, but preferably contain 2 to 12 carbon atoms. They may be linear or branched, but linear alkenyl groups are preferred. Examples of suitable groups having aliphatic unsaturated bonds include alkenyl groups such as vinyl, allyl, butenyl, pentenyl, and hexenyl groups, with vinyl and / or allyl groups being particularly preferred. Groups having aliphatic unsaturated bonds may be found pendant along the polymer chain or at the chain ends, but it is preferred that the groups are at the chain ends.
[0021] The state of component (A) at 25° C. is not limited, but is preferably a liquid. Component (A) preferably has a viscosity of 1 to 100 Pa·s at 25° C. In this specification, the viscosity can be measured in accordance with JIS K7117-1: Plastics-Liquid, Emulsions or Dispersions Resins-Method of Measuring Apparent Viscosity by Brookfield Rotational Viscometer, or ISO 2555: Plastics Resins in the Liquid State or as Emulsions or Dispersions Determination of Apparent Viscosity by the Brookfield Teste Method.
[0022] The molecular weight of component (A) is not limited, but the number average molecular weight (GPC method, polystyrene equivalent) is preferably 100,000 or less, more preferably about 500 to 100,000. In particular, a liquid having a fluidity of about 1,000 to 40,000 is preferred from the viewpoint of ease of handling.
[0023] Exemplary commercially available polyolefins are liquid polybutadienes Ricon® 130, 131, 131MA10, 134, 138, and 181; Poly bd® R-45-V available from CRAY VALLEY.
[0024] The content of component (A) is in the range of 20 to 80 mass % or 25 to 80 mass % based on the total mass of components (A) to (D), respectively. This is because when the content of component (A) is equal to or higher than the lower limit of the above range, the curability of the composition is good, whereas when the content of component (A) is equal to or lower than the upper limit of the above range and the content of component (B) is higher, the phase change properties of the cured product are good.
[0025] Component (B) is a wax compatible with component (A) and acts as a phase change material that undergoes a reversible solid-liquid phase change at or below the maximum operating temperature of the electronic device. Component (B) has a melting point of 30 to 100°C, preferably 35 to 100°C, 35 to 80°C, or 35 to 70°C. Component (B) solidifies when cooled below its melting point, thereby maintaining intimate contact between the heat-generating electronic component and the heat spreader. In this specification, the melting point (°C) may be measured by a differential scanning calorimeter (DSC) in accordance with ASTM D3418. The compatibility between components (A) and (B) may be determined by ASTM D6038:Standard Test Methods for Determining the Compatibility of Resin / Solvent Mixtures by Precipitation Temperature (Cloud Point).
[0026] Exemplary waxes of component (B) include paraffin wax, microcrystalline wax, and polyethylene wax. Preferred waxes are 12 ~C 25 It is paraffin wax.
[0027] The content of component (B) is in the range of 10 to 75 mass%, alternatively 20 to 75 mass%, alternatively 30 to 75 mass%, or alternatively 40 to 75 mass%, based on the total mass of components (A) to (D). This is because when the content of component (B) is equal to or greater than the lower limit of the above range, the phase change properties of the cured product are good, whereas when the content of component (B) is equal to or less than the upper limit of the above range, the curability of the composition is good.
[0028] Component (C) is an organopolysiloxane having at least two silicon-bonded hydrogen atoms per molecule. The organic groups in the organopolysiloxane of component (C) are exemplified by monovalent hydrocarbon groups free of aliphatic unsaturation, such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, and other alkyl groups having 1 to 12 carbon atoms; phenyl, tolyl, xylyl, naphthyl, and other aryl groups having 6 to 12 carbon atoms, with methyl and phenyl being the most typical.
[0029] The organopolysiloxanes of component (C) are selected from the group consisting of methylphenylpolysiloxanes having both molecular chain ends end-capped with dimethylhydrogensiloxy groups; methylphenylsiloxane-dimethylsiloxane copolymers having both molecular chain ends end-capped with dimethylhydrogensiloxy groups; methylphenylsiloxane-methylhydrogensiloxane copolymers having both molecular chain ends end-capped with trimethylsiloxy groups; methylphenylsiloxane-methylhydrogensiloxane-dimethylsiloxane copolymers having both molecular chain ends end-capped with trimethylsiloxy groups; (CH3)2HSiO 1 / 2 Siloxane units represented by C6H5SiO 3 / 2 Organopolysiloxane copolymers composed of siloxane units represented by the formula (CH3)2HSiO 1 / 2 Siloxane unit represented by (CH3)3SiO 1 / 2 Siloxane units represented by the formula: and C6H5SiO 3 / 2 Organopolysiloxane copolymers composed of siloxane units represented by the formula (CH3)2HSiO 1 / 2 Siloxane unit represented by (CH3)2SiO 2 / 2 Siloxane units represented by the formula: and C6H5SiO 3 / 2 Organopolysiloxane copolymers composed of siloxane units represented by the formula (CH3)2HSiO 1 / 2 Siloxane unit represented by C6H5(CH3)2SiO 1 / 2 Siloxane units represented by the formula: and SiO 4 / 2Organopolysiloxane copolymers composed of siloxane units represented by (CH3)HSiO 2 / 2 Siloxane units represented by C6H5SiO 3 / 2 and mixtures of two or more of the foregoing.
[0030] The content of component (C) is in the range of 1 to 20 mass%, alternatively 1 to 15 mass%, alternatively 1 to 10 mass%, or alternatively 2 to 10 mass%, based on the total mass of components (A) to (D). This is because when the content of component (C) is equal to or higher than the lower limit of the above range, the composition can be cured sufficiently, whereas when the content of component (C) is equal to or lower than the upper limit of the above range, the heat resistance of the cured product is improved.
[0031] Component (D) is a hydrosilylation catalyst used to accelerate the curing of the composition, and examples of component (D) include platinum-based catalysts, rhodium-based catalysts, and palladium-based catalysts. Component (D) is typically a platinum-based catalyst so that the curing of the composition can be dramatically accelerated. Examples of platinum-based catalysts include platinum fine powder, chloroplatinic acid, alcohol solution of chloroplatinic acid, platinum-alkenylsiloxane complex, platinum-olefin complex, and platinum-carbonyl complex, with platinum-alkenylsiloxane complex being the most typical.
[0032] The content of component (D) in the composition is an amount effective for promoting the curing of the composition. Specifically, in order to sufficiently cure the composition, the content of component (D) is typically an amount such that the content of the catalytic metal in component (D) is 0.01 to 500 ppm, alternatively 0.01 to 100 ppm, alternatively 0.01 to 50 ppm, by mass, relative to the composition.
[0033] The material may further include (E) at least one inorganic filler. Exemplary fillers of component (E) include flame retardant fillers and thermally conductive fillers. Component (E) may be any combination of any one or more thermally conductive fillers selected from metals, alloys, nonmetals, metal oxides, metal hydroxides, or ceramics. Exemplary metals include, but are not limited to, aluminum, copper, silver, zinc, nickel, tin, indium, and lead. Exemplary nonmetals include, but are not limited to, carbon, graphite, carbon nanotubes, carbon fibers, graphene, and silicon nitride. Exemplary metal oxides, metal hydroxides, and ceramics include, but are not limited to, alumina, aluminum nitride, aluminum hydroxide, boron nitride, zinc oxide, and tin oxide. Desirably, component (E) is any combination of any one or more selected from the group consisting of alumina, aluminum, zinc oxide, boron nitride, aluminum nitride, and aluminum hydroxide. Even more preferably, component (E) is any combination of one or more fillers selected from aluminum hydroxide having an average particle size of 1-15 μm, spherical aluminum particles having an average particle size of 5-15 μm, spherical aluminum particles having an average particle size of 1-3 μm, and zinc oxide particles having an average particle size of 0.1-0.5 μm. The average particle size of the filler particles is determined as the median particle size (D50) using a laser diffraction particle size analyzer (CILAS920 particle size distribution analyzer or Beckman Coulter LS 13 320 SW) according to the operating software.
[0034] The amount of component (E) is not limited, but is preferably 50% by mass or less of the composition, because the phase change properties of the cured product are good when the content of component (E) is equal to or less than the upper limit of the above range.
[0035] The composition may further comprise additional components such as one or more additives, which may include, but are not limited to, antioxidants, antistatic agents, color enhancers, dyes, lubricants, fillers such as TiO2 or CaCO3, opacifiers, nucleating agents, pigments, processing aids, UV stabilizers, antiblocking agents, slip agents, tackifiers, fire retardants, antimicrobial agents, odor reducing agents, antifungal agents, and combinations thereof.
[0036] The composition can be prepared by mixing all of the components at ambient temperature. Any of the mixing techniques and devices described in the prior art can be used for this purpose. The specific device used will depend on the viscosity of the components and the final composition. It may be desirable to cool the components during mixing to avoid premature curing.
[0037] The cured product of the present invention can be obtained by curing the above-mentioned curable polyolefin composition. The cured product of the present invention can be used as a thermal interface material or encapsulant for electronic devices. EXAMPLES
[0038] The curable polyolefin composition and the cured product of the present invention will be described in detail using examples and comparative examples. However, the present invention is not limited to the description of the examples listed below.
[0039] <Curing time> The curing time was measured by a durometer test method. The time required for the hardness change to stabilize (change less than 5 Shore A) after the start of curing was set as the curing time. The hardness test used Shore A according to ASTM D 2240.
[0040] <Phase change temperature and enthalpy of phase change> The temperature of phase change and the enthalpy of phase change were tested by DSC on a DSC-Q2000 instrument according to ASTM D3418. The method is carried out under the following conditions: -1: Equilibrate at 0.0℃ -2: Data storage: On -3: 10.0°C / min gradient to 150.0°C -4: Isothermal for 5.00 min -5: marks the end of cycle 1 -6: 10.0°C / min gradient to 0.0°C -7: Isothermal for 5.00 min -8: marks the end of cycle 2 -9: 10.0°C / min gradient to 150.0°C -10: marks the end of cycle 3 -11: End of method
[0041] Data was collected during the heating scan step of cycle 2 as in FIG.
[0042] <Wax leakage after thermal cycling> Wax leakage was evaluated according to the following procedure. (1) 20 g of the curable polyolefin composition is placed in a 40 mL sealable transparent glass jar. (2) Heating the composition to cure it (3) Then, heat cycle from 25°C to 80°C at least 10 times. (4) Tare a disposable aluminum pan and place an inverted open glass jar on the aluminum pan at 100° C. for 10 minutes, then remove the glass jar and weigh the aluminum pan. (5) Calculate the mass % of the leaked components relative to the total composition mass. If the mass % of the leaked components is greater than 3 mass %, wax leakage is identified as "observed", otherwise it is identified as "none".
[0043] [Examples 1 to 14 and Comparative Examples 1 to 3] The following components were used to prepare the curable polyolefin compositions shown in Table 1. Component (A) and component (B) were mixed uniformly at 60° C. Then, component (C), component (D), and optionally component (D) were added and mixed with high speed mixing at a speed of 1000 rpm for 20 seconds.
[0044] The following components were used as component (A): Component (a-1): Liquid polybutadiene (trade name: Ricon (registered trademark) 131, commercially available from TOTAL CRAY VALLEY; Mn = 4,500) Component (a-2): Liquid hydroxyl-terminated polybutadiene (trade name: Poly bd® R45 V, commercially available from TOTAL CRAY VALLEY; Mn=2,800) Component (a-3): Liquid polybutadiene (trade name: Ricon (registered trademark) 131MA10, commercially available from TOTAL CRAY VALLEY; Mn = 5,000) Component (a-4): Liquid polybutadiene (trade name: Ricon (registered trademark) 181, commercially available from TOTAL CRAY VALLEY; Mn = 3,200)
[0045] The following components were used as component (B): Component (b-1): Paraffin wax (commercially available from SCRC; melting point = 52-54°C) Component (b-2): Docosane (commercially available from SCRC; melting point = 43-47°C)
[0046] The following components were used as component (C): Component (c-1): Trimethylsiloxy-terminated dimethylsiloxane methylhydrogen siloxane copolymer (SiH content = 0.78% by mass) Component (c-2): Tetrakis(dimethylsilyl)silane (SiH content = 1.23% by mass)
[0047] The following components were used as component (D): Component (d-1): 1,3-divinyl-1,1,3,3-tetramethyldisiloxane solution of Pt complex with 1,3-divinyl-1,1,3,3-tetramethyldisiloxane (Pt content = 5,000 ppm)
[0048] The following components were used as component (E): Component (e-1): Aluminum hydroxide filler having an average particle size of 15 to 25 μm (trade name: MARTINAL® ON-320, commercially available from HUBER MARTINSWERK) Component (e-2): Spherical aluminum nitride filler having an average particle size of 30 μm (product name: ANF-30, commercially available from MARUWA) Component (e-3): Spherical aluminum oxide filler having an average particle size of 35 μm (trade name: A-ST-60, commercially available from ZRI)
[0049] [Table 1]
[0050] [Table 2]
[0051] [Table 3]
[0052] Curing performance is important for the encapsulant. As shown in Table 1, the comparative compositions CE1 and CE3 did not cure due to the absence of component (C) as a crosslinker and the excessive addition of component (B). When the amount of component (A) added is more than 20% by weight of the total amount of components (A) to (D), the curing performance is good (IE1 to IE9), and the respective curing times of all the present compositions are less than 3 hours at 60°C, regardless of the different components (A) (IE9, IE10 and IE11) and different components (C) (IE7 and IE8) and different components (E) (IE13 and IE14). The enthalpy of phase change (J / g) is another important property of the encapsulant. The respective enthalpies of phase change for the present compositions ranged from 20 to 140 J / g, which was dependent on the type and amount of wax (IE1 to IE14) added. However, when the wax loading was less than 10% by weight of the total amount of components (A)-(D) (CE2), the enthalpy of phase change (J / g) was too low to be used as a PCM heat sink. Inorganic fillers can also be used in the composition, which does not affect the cure and phase change properties, and loadings can be as high as 47% by weight of the composition (IE1). Furthermore, the cured product of the composition had no wax leakage after thermal cycling from 25 to 80°C.
[0053] Industrial Applicability The curable polyolefin compositions of the present invention can be cured to form phase change materials that prevent leakage / extrusion during thermal cycling, and are therefore useful as encapsulants or sealants for electronic devices such as mobile phones.
Claims
1. 1. A curable polyolefin composition comprising: (A) a polyolefin having at least two aliphatic unsaturated bonds per molecule; (B) a wax having a melting point of 30 to 100°C; (C) an organopolysiloxane having at least two silicon-bonded hydrogen atoms per molecule; (D) a catalytic amount of a hydrosilylation reaction catalyst, A curable polyolefin composition, wherein the content of component (A) is 20 to 80 mass %, the content of component (B) is 10 to 75 mass %, and the content of component (C) is 1 to 20 mass %, each based on the total mass of components (A) to (D).
2. 2. The curable polyolefin composition of claim 1, wherein component (A) is a polybutadiene.
3. 2. The curable polyolefin composition of claim 1, wherein component (B) is a wax selected from paraffin wax, microcrystalline wax, or polyethylene wax.
4. 10. The curable polyolefin composition of claim 1, further comprising (E) at least one inorganic filler.
5. 5. The curable polyolefin composition of claim 4, wherein component (E) is at least one inorganic filler selected from a flame retardant filler or a thermally conductive filler.
6. 5. The curable polyolefin composition of claim 4, wherein the content of component (E) is up to 50% by weight of the composition.
7. A cured product obtainable by curing the curable polyolefin composition according to any one of claims 1 to 6.
Citation Information
Patent Citations
Crosslinked polyolefin resin composition and its production
JP1986060727A
Curable composition
JP1992023867A
Polyolefin composition
JP2000087002A
Curable composition for encapsulant for luminous display unit and production of luminous display unit
JP2000136275A
Flame-retardant resin composition
JP2000290462A